Penatalaksanaan Diet Pada Pasien Cerebrovascular Accident di Rumah Sakit Baptis Kediri - Defy Fitriani, Defy Fitriani; Palupi, Mirthasari; Mar'atus Sholichah, Rizka; Kuswinarti, Enny; arif budiman, frenky (STIKES dan AKZI Karya Husada Kediri, 2025)
Degenerative diseases, such as stroke or cerebrovascular accident (CVA), have increased in prevalence in Indonesia. Risk factors such as hypertension, diabetes, and unhealthy eating habits are major contributors. Proper nutritional management, including a low-salt and high-potassium diet, plays a crucial role in the rehabilitation of stroke patients. This study aims to evaluate the effectiveness of the diet provided to CVA patients at Baptis Kediri Hospital. A descriptive study with a case study approach was used. The study was conducted on Mr. A, a 49-year-old male patient diagnosed with intracerebral hemorrhage. Data were collected through four-day physical examinations, clinical data, and nutritional care. The results showed that the patient's blood pressure decreased after implementing a low-salt and high-potassium diet, although blood pressure remained fluctuating. The patient's energy and nutrient intake were calculated based on their daily energy needs adjusted to their physical condition. Providing a proper diet according to nutritional needs improved the patient's intake and potentially accelerated recovery. The study concludes that proper nutritional management plays a significant role in stroke rehabilitation by meeting the patient's calorie, protein, fat, and carbohydrate requirements.